Profil Kasus Endometriosis di RSUD Arifin Achmad Provinsi Riau Periode 1 Januari 2012 – 31 Desember 2016 - Dini Fatimah; Imelda E.B Hutagaol; Ilhami Romus (Jurnal Ilmu Kedokteran, 2018)
Endometriosis is endometrial tissue (glands and stroma) that grow outside of the uterus. The goal of this research was to see the profile of endometriosis cases in Arifin Achmad general hospital in Riau province. The research method used is descriptive with cross-sectional approach. Based on patient characteristics, highest education was SMA (47,9%), majority patients cames from Pekanbaru city (58,8 %), the patients were at reproductive age (92.6%), most patients were nullipara (54.8%). Anatomical location were 45.1% located in the ovarium. The most common clinical symptom was dysmenorrhea (36.2%), 49.5% were stage 4, and the most frequently performed was laparotomy (71.8%). The conclusionof this study were endometriosis found primarily in reproductive and nulliparous ages, the most common anatomic location was in the ovarium and classified in stage 4, the most clinical symptom was  dysmenorrhea, and the most common operative action was laparotomy.